PENINGKATAN KAPASITAS KADER DALAM DETEKSI RISIKO KURANG ENERGI KRONIK (KEK) PADA IBU HAMIL MELALUI PELATIHAN PENGUKURAN LINGKAR LENGAN ATAS DI POSYANDU DAHLIA DESA KABASIRAN - Harna, Harna; Asmirajanti, Mira; Rahmawati, Rahmawati; Nurshabrina, Nurshabrina; Permatasari, Bella Prisca; Ramadhanti, Kaylifa (Jurnal Abdi Insani, 2024)
Chronic Energy Deficiency (CED) in pregnant women is a serious nutritional problem in Indonesia. This condition can affect maternal health and fetal development. MUAC measurement becomes important as an indicator of the nutritional status of pregnant women and as a predictor of CED risk. This community service activity aims to increase the capacity of Posyandu cadres in detecting CED risk through training in Mid-Upper Arm Circumference (MUAC) measurement. The research method includes socialization, comprehensive training, technology application, evaluation, and program sustainability. The activity was carried out at Posyandu Dahlia, Kabasiran Village, involving 30 cadres. Results showed a significant increase in cadres' understanding and skills, especially in MUAC measurement and result interpretation (p<0.05). This improvement is reflected in test scores and direct performance observations. The program successfully strengthened the role of cadres as a link between the community and formal health services, enhancing the ability for early detection of CED and nutrition education for pregnant women. The implementation of this program is expected to have long-term impacts, including a decrease in CED prevalence and improved health of pregnant women.